Evaluating electronic music technology resources for music therapy - Krout, Robert; Bastable, Barbara L.; Dalton, Thomas A. (Barcelona Publishers LLC, 2015)
Designed for students, interns, clinicians, educators, and supervisors, this manual provides a field-tested set of systematic way of evaluating the usefulness of electronic music applications in a music therapy setting. Four categories are described and evaluated: general or stand-alone products, computer software, electronic keyboards, and tablet computer applications (apps). The evaluations are detailed and each focuses on one of the categories. Each form helps the reviewer to note and evaluate basic product information and intended users, product details, considerations for use by their clients, and product rating on specific criteria and recommendation to use/not use the product. Six sample product reviews are included, as well as a glossary of terms.
Keywords: Music therapy; Electronic music